Fast Loans – Method of Raising Liqyudity or Reason Rising Debt - Jakubczyk, Beata; Lewandowska, Justyna (Journal of Finance and Financial Law, 2014)
This article describes the essence of fast, instant cash loans which can raise liquidity or be the cause of growing indebtedness. The purpose of this article is to show the advantages and disadvantages of fast loans and attempt to compare different loan options available to the client on the Polish market. In this paper an analysis of the costs, repayment terms and specificities loan offers, which showed that fast loans perfect solution for those conscious consequences borrowings.